Targeted agents in cancer. (January 2023) - Fitzgerald, Helen; Kumar, Satish
Abstract: Non-cytotoxic systemic treatments are a major component of systemic anti-cancer treatment. Targeted therapies are used to treat multiple tumour sites in both potentially curative and palliative settings and can be used in combination with chemotherapy, surgery and radiotherapy. Agents can have specific or multiple targets inhibiting cellular proliferation and cell growth, and inducing cellular arrest and apoptosis. Patients must be closely observed on treatment; adverse effects can be class- or agent-specific. Despite high activity levels, cancer cells eventually develop mechanisms of resistance against targeted therapy.